EAPH-16. DISCOVERY OF CT-179: A SMALL MOLECULE INHIBITOR OF THE OLIG2 TRANSCRIPTION FACTOR WITH POTENT ANTI-TUMOR IN PEDIATRIC BRAIN CANCER. Issue 2 (22nd June 2018) - Johns, Terrance; Greenall, Sameer; Chen, Charlotte; Day, Bryan
Abstract: OLIG2 is a protein transcription factor (TF) expressed exclusively in progenitor cells in the brain and spinal cord during development and is re-expressed in most adult and pediatric brain cancers. Expression of OLIG2 drives the growth, invasiveness, and resistance to radiation in brain cancer cells and tumors in animal models. CT-179 is a novel small molecule (M.W. 397) that is a disruptor of OLIG2 function. We now show that CT-179 profoundly inhibited the growth, and induced apoptosis, in a range of patient-derived adult and pediatric cell lines at low nM concentrations, including diffuse intrinsic pontine glioma and medulloblastoma. Treated cells showed substantial degradation of OLIG2 protein that was associated with G2/M arrest and mitotic catastrophe. CT-179 also caused significant down-regulation of receptor tyrosine kinases associated with tumorigenicity, including EGFR and PDGFR. Orally administered CT-179 (20 mg/kg) crossed the blood-brain-barrier of intact mice reaching levels sufficient to inhibit patient-derived xenografts. Indeed, patient-derived xenografts in mice was significantly inhibited by CT-179. Our studies have provided the impetuses for moving CT-179 into the clinic as a novel therapy for patients with a range of brain cancers.